PENINGKATAN PRESTASI DAN MOTIVASI BELAJAR MATEMATIKA MELALUI PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS SOCIAL EMOTIONAL LEARNING - Titin Ardiyanti; Susanti, Vera Dwi; Nartini (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2025)
This research is conducted due to the low learning motivation of students, which affects their mathematics academic performance. This is caused by differences in students' backgrounds, which can trigger adolescent issues such as choosing friends, refusing advice, and so on. As a result, some students become reluctant to interact and their motivation in learning decreases. The purpose of this study is to find solutions or strategies that can be applied to improve students' learning motivation, particularly in mathematics, so that their academic achievement can improve. Additionally, this research is expected to provide an overview of the importance of positive social interactions among students to support a more effective learning process. to improve students' achievement and learning motivation through the Problem Based Learning model with the Social Emotional Learning (SEL) approach in class VIII in mathematics lessons at SMPN 1 Madiun. This type of research is classroom action research which is carried out with stages in each cycle including planning, implementation, observation, and reflection. The subjects of the study were 32 students in class VIII B at SMPN 1 Madiun. The instruments used in this study were observation sheets, learning motivation questionnaires, initial ability tests and student worksheets. The data analysis used was qualitative and quantitative data analysis. This study was conducted in 2 cycles, and each cycle consisted of 2 meetings. The results of this study showed an increase in achievement from an average in the first cycle of 71.87% to 81.25%. In addition, there was also an increase in students' learning motivation from the beginning of 51.04% to 69.78% in cycle I and to 81.22% in the second cycle.